Measurement of the CKM angle γ in B± → DK± and B± → Dπ± decays with D → KS0h+h−; Journal of High Energy Physics; Vol. 2021, iss. 2 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen